Characterization of Corrosion Behavior of Painted Galvanized Steel under Accelerated Conditions - Vázquez Rodríguez, Francisco Javier; De La Garza Garza, M.; Gaona Tiburcio, Citlalli; Maldonado Bandala, Erick; Baltazar Zamora, Miguel Ángel; Garza C. R. de, J.; García, R.O.; Garza Montes de Oca, Nelson Federico; Ramírez R., J.L.; Almeraya Calderón, Facundo (Electrochemical Science Group, 2015)
In the present study three systems of carbon steel (1008) are evaluated, which were provide of two corrosion control methods, barrier and cathodic protection (painted and galvanized respectively) commonly used in the construction industry. They were evaluated under accelerated conditions exposed in fog chamber, according to ASTM B-117, which specifies continues exposition of sodium chloride at 5% and 35 °C. The main aim of the research was to characterize the corrosion resistance and to determine the degradation mechanism under test’s conditions. The results after 1080 and 3500 hours of exposure are presented, with adhesion measure (ASTM D-3359) and scratch resistance measure (D-1654) for each exposure time, as well as the characterization of corrosion attack through the mapping analysis of Scanning Electron Microscope / Energy Dispersive X-ray. According to the results it is proposed that the corrosion of the systems under study begins at galvanized – metal base interface. Later advances due to formation of porous layer of zinc hydroxi-chloride, which it’s characteristic of environments with chloride ions, forming zinc’s corrosion products like zinc oxide and zinc hydroxide on the porous layer until iron starts to dissolve, producing iron oxide and iron oxy-hydroxide on the zinc’s corrosion products and porous layer.